Enhanced anharmonic phonon coupling and decay dominated by low‐energy phonons in CdS nanowires. (22nd July 2019) - Iqbal, Muhammad Faisal; Saeed, Sara; Wu, Lingling; Zhu, Peng; Wang, Deliang
Abstract: Low‐energy optical phonons with energy in the order of that of acoustic phonons are readily populated at room temperature, and therefore, they play a key role in thermal, electronic, and thermo‐electric fundamental processes in a solid material. High‐quality crystalline cadmium sulfide (CdS) nanowires with a diameter of several tens of nanometer and a length up to several micrometers (3–5 μm) demonstrate strong exciton–phonon coupling. This strong coupling interaction allows us to observe low‐energy optical phonons and their anharmonic couplings to high‐energy phonon modes. In this study, second and higher order multiphonons related to the E 2 low phonon were observed in near resonance Raman scattering condition (excitation wavelength of 532 nm). The clear observation of the multiphonon modes makes it possible to study composite phonon anharmonic decay. The experimental results show that low‐energy phonons (both optical and acoustical) dominate anharmonic phonon decay in CdS. Abstract : High‐quality crystalline CdS nanowires with a diameter of several tens of nanometer and a length up to several micrometers (3‐5 μm) demonstrate strong exciton–phonon coupling. This strong coupling interaction allows us to observe low‐energy optical phonons and their anharmonic couplings to high‐energy phonon modes. The clear observation of the multiphonon modes makes it possible to study composite phonon anharmonic decay. Compared with the single 1LO phonon mode, the composite 1LO − 2 E 2 low mode showed dramatically longer phonon lifetime.